Static Mechanical Properties and Failure Modes of Layered Sandstones in Freeze-thaw Cycles. Issue 1 (November 2020) - Chang, Sen; Xu, Jinyu; Wu, Yunquan; Wang, Tengjiao; Liu, Gaojie; Huang, He
Abstract: Because the underground space in the alpine area is often in the freezing and thawing cycle state, as well as the layered rock is widely found in nature and the mechanical properties are complex, the mechanical properties of the lower rock in the freeze-thaw cycle are directly related to the development and utilization of the underground space in the alpine area. Based on the electro-hydraulic servo pressure tester, the static compression test of freeze-thaw damage specimen was carried out to study the strength, deformation, failure mode and anisotropy characteristics of the layered sandstone in freeze-thaw cycle condition. Also, the influence of freezing and thawing action and layered structure on the static mechanical properties and the mechanism of action were analysed. Finally, we obtained the following conclusions: The stress-strain curves of vertical and parallel bedding sandstones under freezing and thawing conditions can be roughly classified into compaction phase, elastic phase, plastic yielding stage and failure stage, and with the increase of freezing and thawing times, the peak stress and elastic modulus of layered sandstone samples decrease gradually; compared with vertical bedding samples, the mechanical parameters of parallel bedding samples deteriorate faster under freeze-thaw cycles; the deterioration of mechanical parameters of parallel layered specimens is faster under the condition of freeze-thaw cycle; the anisotropy index Rc of the intensity increased from 1.07 in 0 freeze-thaw cycle to 1.46 in 40 freeze-thaw cycles, and the intensity anisotropy became more significant as the number of freeze-thaw cycles increased.; when the number of freeze-thaw cycles is less than 10 times, the vertical bedding test specimen breaks the main crack at a certain angle (about 30°), showing shear failure through multiple bedding, while when the number of freeze-thaw cycles increases, the main crack tends to be parallel to the loading direction; parallel bedding samples always exhibit splitting failure along the bedding. The test results can provide theoretical support for the development of special underground space such as alpine and freeze-thaw areas.